A virtual tutor for children with autism. Issue 1 (20th March 2017) - Herring, Paul; Kear, Karen; Sheehy, Kieron; Jones, Roger
Abstract : Purpose: The picture exchange communication system (PECS) is an established communication intervention for non-verbal children with autism. The purpose of this paper is to present an evaluation of a computer-based PECS approach, in which young non-verbal children with autism respond to an on-screen "virtual tutor" through the manipulation of picture/symbol cards. The paper presents research to investigate how the virtual tutor's voice influences the children's participation and performance. Design/methodology/approach: Eight non-verbal children between six and nine years old and with a diagnosis of autism were presented with a series of computer-based activities, using a virtual tutor with either a natural or synthetic voice, in two separate sessions. Data were gathered using a within-participants counterbalanced design to control against variations between individuals and effects of presentation order. Findings: Analysis of the children's responses suggest that they were able to use the system more effectively when the virtual tutor had a synthetic voice, rather than a human voice. The findings demonstrate that a computer-based virtual tutor can provide an engaging method of supporting symbol-based communication for non-verbal children with autism, and that a synthetic voice type was preferable for the sessions undertaken. Originality/value: Investigations of voice type and its influence on non-verbal children's participation and performance have so far provided inconclusive results (Ramdoss, 2013). This research suggests that the voice type is an important feature of the learning experience of non-verbal children with autism, and can have a significant influence on their participation and performance in virtual tutor-led learning.